Nutrition, the brain and prolonged exercise - Watson, P. (European Journal of Sport Science, 2008)
Possible peripheral mechanisms of fatigue have been widely documented, including the depletion of muscle glycogen and the loss of body fluids. The notion that the brain may be intimately involved in the fatigue process is not a new one, but recently possible neurobiological mechanisms involved in this response have been investigated. Changes in central neurotransmission occur during exercise that may result in feelings of tiredness, lethargy, and a loss of motivation to continue exercise, contributing to the development of fatigue. There is evidence that manipulation of the neurotransmitters serotonin, dopamine, and noradrenaline, through the administration of pharmacological agents, may delay the onset of fatigue during prolonged exercise, particularly when performing in a warm environment. Supplementation with branched-chain amino acids and tyrosine can influence perceived exertion and some measures of mental performance, but the results of several apparently well-controlled laboratory studies have not demonstrated a positive effect on exercise capacity under temperate conditions. The ergogenic effects of carbohydrate and caffeine are well documented, but often little attention is paid to the central effects of these nutrients. Carbohydrate ingestion has been demonstrated to alter brain activity and cerebral metabolism, factors that may be important in the development of fatigue and the maintenance of skill performance. There is strong evidence for a positive effect of caffeine on exercise performance, with recent data highlighting the role of central adenosine as a mediator of this response.